Assessment of phenolic, volatile profiles and in vitro digestibility of different pine cone decoctions - Ozkan, Kubra; Bekiroglu, Hatice; Cebi, Nur; Tigli-Kaytanlioglu, Hatice; Fakir, Huseyin; Sagdic, Osman (SPRINGER, 2026)
Phenolics are bioactive compounds known for their health-promoting properties, including antioxidant, anti-inflammatory, and potential protective effects against chronic diseases. They are also valued in the food industry for their role in enhancing nutritional quality and shelf life. This study aimed to evaluate the physicochemical properties, phenolic and volatile profiles, and antioxidant capacities of five pine cone powders (Pinus sylvestris, Pinus nigra, Pinus pinea, Pinus halepensis, and Pinus brutia) and their decoctions, as well as to investigate the changes in bioactive compounds during in vitrogastrointestinal digestion. The predominant volatile compounds in the decoctions were alpha-pinene, limonene, and pinocarveol. Total phenolic content (TPC) varied from 14.10 to 83.03 mg GAE/g dry weight, with P. halepensis decoction exhibiting the highest levels, followed by P. sylvestris. Quercetin emerged as the principal phenolic compound, along with caffeic acid, kaempferol, gallic acid, protocatechuic acid, and catechin. While P. halepensis showed high TPC and antioxidant capacity, its bioaccessibility index (BI %) was not consistently the highest. Notably, all decoctions except P. pinea maintained higher TPC and antioxidant levels throughout the intestinal phase, retaining 26.20%-37.47% of their initial phenolic content. These findings highlight the potential of pine cone decoctions as functional ingredients rich in phenolic and volatile compounds, suggesting applications in health-promoting foods and nutraceuticals.
Keywords: Cone decoction; Phenolics; Volatile compounds; Antioxidant capacity; Bioaccessibility; CHEMICAL-COMPOSITION; ANTIOXIDANT ACTIVITY; EXTRACTS; CAPACITY; BARK; Food Science & Technology